Emotional Intelligence Competence and Teacher Performance: A Case Study of Post Certification Teacher - imam subqi (IJIP : Indonesian Journal of Islamic Psychology, 2023)
This study aims to determine the performance of teachers after PPG Daljab LPTK UIN Salatiga certification in emotional maturity, emotional competency, emotional sensitivity by using qualitative research. The results of this study indicate that: first, the performance of post-certification teachers in emotional maturity is that teachers are able to control their emotions well when carrying out tasks at school, are more responsible, have a sense of empathy, are aware of their own mistakes, admit their weaknesses, and are able to adapt. Second, the teacher's performance in individual skills, being able to control emotions, maintain self-esteem, always respond to problems wisely, can control the ego. Third, the post-certification teacher's performance in emotional sensitivity, the teacher has empathy for the people around him, improves personal relationships, is able to communicate warmly, understands when to act emotionally and when to be rational. The contribution of this study is able to explain that the performance of teachers after teacher certification in emotional intelligence competency in schools and madrasas has an impact on increasing performance and increasing teacher professionalism.